Efektivitas Cognitive Behaviour Therapy dalam Mengurangi Gejala Post Traumatic Stress Disorder: Systematic Review - Siti Kotijah; I Ketut Andika Priastana (Poltekkes Kemenkes Maluku, 2020)
Post traumatic stress disorder (PTSD) is a mental disorder that occurs after an individual is exposed to a very threatening or terrible event. Most individuals exposed to trauma require resilience and a deep recovery period. Psychosocial interventions such as cognitive behavioral therapy (CBT) is one of the efforts that can be given to PTSD patients with the aim of reducing the symptoms of PTSD that appear so that it does not interfere with social functions and daily life. This study aims to determine the effectiveness of internet-based and manual Cognitive Behavior Therapy (CBT) in reducing the symptoms of Post Traumatic Stress Disorder (PTSD). Sources of data obtained from Pubmed, Sciencedirect, Wiley and Ebsco. Inclusion Criteria: research studies using the RCT approach; studies in PTSD patients in the age range of children and adults; studies with Cognitive Behavior Therapy (CBT) interventions, either as independent interventions or in combination with other interventions. Appraisal studies use the critical appraisal skills program (CASP), and the synthesis method uses PICO modifications. The results of this study Cognitive Behavior Therapy (CBT) had a significant effect on reducing the symptoms of PTSD. Cognitive Behavior Therapy (CBT) has a significant influence in reducing the symptoms of PTSD so that it can be applied as an effort to improve the quality of life of post-traumatic individuals.